Drug-induced hepatitis, drug-induced autoimmunity or classical autoimmune hepatitis: How can we differentiate ? - Dilek OĞUZ,; Engin ALTINTAŞ,; Sabite KACAR,; Yasemin ÖZDERİN ÖZİN,; Orhan SEZGİN,; Neslihan İNCİ ZENGİN, (Turkish Journal of Gastroenterology, 2019)
-